Business Analysis of Tilapia (Oreochromis niloticus) at Pond of Fast Water in Koto Tangah District, Padang City, West Sumatera Province - Munthe, Desi Natalia; Sofyani, Tince; Hendrik, Hendrik (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This research was conducted in two Villages, Balai Gadang Village and Lubuk Minturun Village, Koto Tangah District, Padang City, West Sumatera Province with the aim of calculating the amount of investment, revenue, profit and feasibility level of tilapia fish farming of water pouring down based on financial (financial) aspects using analysis of investment, revenue, profit, Revenue Cost of Ratio (RCR), financial rate of return (FRR), and payback period of capital (PPC). The method used in this study is a survey method. Data collection was carried out by observation, interviews and direct documentation with 7 tilapia cultivators. The results showed that the average investment issued by tilapia cultivators on a small scale was IDR88.432.667, medium scale was IDR147.275.000 and large scale was IDR306.318.000. The average income earned by each cultivator starting from a small scale is IDR214.751.000 with a profit of IDR42.871.133/year, a medium scale of IDR411.033.000 with a profit of IDR93.514.000/year, and a large scale of IDR798.468.000 with a profit of IDR143.500.400/year. The return cost of ratio value obtained for the small scale is 1,25; the medium scale is 1,29; and the large scale is 1,22. The Financial Rate of Return value for each scale is 47,97% small scale, medium scale 62,21%, and large scale 47,76%, and the payback period of capital value for small scale is 2,10 years, medium scale is 1,67 years and large scale 2,15 years